The together teammate : build strong systems, make the work manageable, and stay organized behind-the-scenes - Heyck-Merlin, Maia, 1977- (Jossey-Bass, 2023)
"For many years, teacher training and development has been the focus of attention for schools while the wider body of school support staff have been neglected. As a result of these individuals not being given the training and resources to work at their highest capacity, the abilities of the instructional and management side of the school are being diminished. If schools wish to improve their performance and provide each child with an education that is tailored to their unique learning style, motivations, and needs, the whole school workforce--including support staff--must be equipped to develop their professional skills."--